Body temperature measurement system based on a single board computer and interfaced sensors - Lin, Mingxin (Nanyang Technological University, 2022)
The use of handheld infrared thermometers and temperature scanners for infrared thermal screening has become commonplace worldwide. Its efficiency in the detection of fever was investigated by a full review and meta-analysis. With the help of a standard thermometer, a non-contact portable infrared technology was employed to detect fever.